Current understanding in pathogenesis of atopic dermatitis - Tess McPherson (Wolters Kluwer Medknow Publications, 2016)
There have been advances in our understanding of the complex pathogenesis of atopic eczema over the past few decades. This article examines the multiple factors which are implicated in this process.